2016
DOI: 10.1080/13607863.2016.1247424
|View full text |Cite
|
Sign up to set email alerts
|

People with dementia and carer preferences for home support services in early-stage dementia

Abstract: These preferences concur with emerging evidence on psychosocial interventions in dementia. Support with personal feelings, information and social engagement are important components. Additionally, knowledge of preferences of people with dementia and their carers can identify other attributes that may be important to effectiveness in 'living well' but for which there remains limited evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 40 publications
2
80
0
Order By: Relevance
“…Health and service providers at the 2017/2018 National Research Summit on Dementia Care explicitly called for research to (1) “proactively support” PwD and to reduce the need for “reactive” medical services, (2) implement comprehensive models of care, and (3) validate the effects of different person‐centered care practices on the health and well‐being of PwD . Summit participants also called for additional research supporting informal caregivers' needs, as managing the complexities of dementia care, experiencing frustration, and coping with uncertainty about how to care for their loved one contribute to caregiver stress and burden …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Health and service providers at the 2017/2018 National Research Summit on Dementia Care explicitly called for research to (1) “proactively support” PwD and to reduce the need for “reactive” medical services, (2) implement comprehensive models of care, and (3) validate the effects of different person‐centered care practices on the health and well‐being of PwD . Summit participants also called for additional research supporting informal caregivers' needs, as managing the complexities of dementia care, experiencing frustration, and coping with uncertainty about how to care for their loved one contribute to caregiver stress and burden …”
mentioning
confidence: 99%
“…14 Summit participants also called for additional research supporting informal caregivers' needs, as managing the complexities of dementia care, experiencing frustration, and coping with uncertainty about how to care for their loved one contribute to caregiver stress and burden. [15][16][17][18] To inform the design of proactive, dementia-specific services to prevent or optimally deliver emergency care, we first must better understand how the needs and experiences of PwD, informal caregivers, healthcare providers, and other stakeholders influence ED use among communitydwelling PwD. 6,19 This study explores stakeholders' perspectives on the decisions and drivers influencing ED use and suggestions for effectively addressing unmet needs.…”
mentioning
confidence: 99%
“…This trial was designed to fill a knowledge gap identified by preceding systematic review [ 54 ]. It also took account of another recent study within the programme, which showed that people with dementia prefer advice on memory aids to be provided at home by a trained worker [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that persons with early-stage dementia preferred opportunities for social and recreational activities and support with their personal feelings and concerns. 9 The informal caregivers appeared to prefer support with personal feelings and concerns and information on coping with dementia. 9 Additionally, another UK study by Kampanellou et al 10 that investigated the care preferences of informal caregivers of people with later-stage dementia demonstrated that respite care and daily living assistance were the most preferred attributes for the informal caregivers of people with later-stage dementia.…”
mentioning
confidence: 99%
“…9 The informal caregivers appeared to prefer support with personal feelings and concerns and information on coping with dementia. 9 Additionally, another UK study by Kampanellou et al 10 that investigated the care preferences of informal caregivers of people with later-stage dementia demonstrated that respite care and daily living assistance were the most preferred attributes for the informal caregivers of people with later-stage dementia. However, as the Dutch health-care system differs from the health-care system in the UK, it is unclear if these findings are applicable to the Dutch dementia population.…”
mentioning
confidence: 99%